The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1063/1.4945541
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-treatment on the characteristics of electrospun poly (vinyl alcohol)/chitosan nanofibers

Abstract: Abstract. Electrospun nanofibers have many advantages such as high porosity, easy to be fabricated in various size and high ratio of surface area to volume. This paper presents the preparation of electrospun PVA/Chitosan nanofibers and more specifically focuses on the effect of post-treatment on the permeability and morphology of electrospun PVA/chitosan nanofibers. The mixtures of various concentrations of PVA (6,7,8 wt%)and 2 wt%.chitosan solution (with the ratio of 3:1)were used in electrospun with a consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Appeared peak at 1088 cm -1 belongs CN group. The appeared sharp peak at 1717 cm -1 is attributed to the carboxylate group [55]. Comparing with the control group, a shoulder appeared before the peak at 1087 cm -1 and expanded the appeared peak.…”
Section: Chemical Structurementioning
confidence: 83%
“…Appeared peak at 1088 cm -1 belongs CN group. The appeared sharp peak at 1717 cm -1 is attributed to the carboxylate group [55]. Comparing with the control group, a shoulder appeared before the peak at 1087 cm -1 and expanded the appeared peak.…”
Section: Chemical Structurementioning
confidence: 83%
“…Susanto et al [ 14 ] reported that cross-linking PVA/CS nanofibers with GA resulted in morphological changes to the membrane microstructure, such as an increase in fiber diameter. The addition of GA may produce a more stable membrane because, theoretically, it more efficiently cross-links the free –OH groups of PVA and amine groups of CS to the aldehyde group of GA. Koloti et al [ 23 ] reported that laccase enzymes could be anchored on fibers through the formation of bonds with the abundant peripheral amine groups of CS by using GA as a cross-linker, which resulted in the increased thickness of the laccase-modified membrane surface; this was attributed to the swelling of nanofibers onto which the enzymes were covalently immobilized.…”
Section: Resultsmentioning
confidence: 99%
“…However, electrospinning of CS has some limitations; for example, creating continuous fiber jets during electrospinning is difficult because of the repulsive forces between ionic groups and the high surface tension of the polymer solution given that CS has high viscosity even at moderate concentrations. To overcome these limitations, CS is commonly blended with other polymers for electrospinning, such as polyvinyl alcohol (PVA) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the needle-based approach allows for precise monitoring of the flow rate, minimizes solution waste, and utilizes a small number of jets. Numerous benefits have contributed to the needle-based method's widespread usage [42].…”
Section: Electrospinning Categoriesmentioning
confidence: 99%